SHRIMP U-Pb zircon geochronological and geochemical evidence for Neoproterozoic arc-magmatism along the western margin of the Yangtze Block, South China. - Zhou, M.; Yan, D.; Kennedy, Allen; Li, Y.; Ding, J. (Elsevier Science BV, 2002)
The magmatic and tectonic history of the Yangtze Block and its possible affinity with other Neoproterozoic arc terranes are important in the reconstruction of Neoproterozoic plate tectonics. In the Panxi Belt, adjacent to the eastern margin of the Tibetan Plateau, there are many metamorphic complexes associated with Neoproterozoic granites. These are granitic gneisses of upper greenschist to amphibolite metamorphic facies, which have traditionally been considered the Archean basement of the Yangtze Block, although their origin and age of formation were poorly understood. This study provides the first reliable, SHRIMP U Pb zircon dating results for the gneissic complexes and the Neoproterozoic granites. Three samples of the Kangding gneissic complex yielded identical ages of 79710, 79513 and 79614 Ma. The Gongcai gneissic complex has zircons dated to be 82414 Ma with metamorphic rims of 1773 Ma, whereas the Gezong granite has an older age of 8648 Ma. Other gneissic complexes include the Miyi complex that has a younger age of 7649 Ma. Geochemical data show that the Kangding gneissic complex has arc signatures, representing metamorphic products of Neoproterozoic, arc-related acidic plutons. This scenario suggests subduction of oceanic lithosphere eastward (present-day orientation) underneath the Yangtze Block. There is a well-defined arc assemblage with an identical Neoproterozoic age along the eastern margin of the Yangtze Block. Thus, during Neoproterozoic time, both the western and eastern margins of the block were active arcs separated by the Trans-Yangtze basin. The Yangtze Block must, therefore, have been an isolated continent, although it was presumably located near the Rodinian supercontinent.